Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0021316
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Caloric Restriction

Abstract: Caloric restriction (CR) improves health and increases longevity in organisms from yeast to mammals. Studies in rodent models show that CR suppresses a wide range of diseases that contribute to human morbidity and mortality such as cancer, cardiovascular disease and diabetes. Although the metabolic and physiological changes induced by CR have been investigated for over 70 years, the precise mechanism by which it is able to slow the progression of age‐related degeneration remains a subject of much debate. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…By way of comparison, single-gene mutations were first shown to extend lifespan in worms in 1988 (Friedman and Johnson, 1988), and in rodents in 1996 (Brown-Borg et al, 1996). Whereas most genetic manipulations in rodents have been tested only once, with limited phenotypic assessment, the effects of DR have been tested in hundreds of labs, and its effects on nearly every age-related change have been documented (Baur, 2009; Masoro, 2005; Weindruch and Walford, 1988). The overwhelming conclusion is that DR affects something very fundamental to the aging process, as determined by its effects on disparate age-related diseases, as well as detailed analyses of mortality rates (Yen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By way of comparison, single-gene mutations were first shown to extend lifespan in worms in 1988 (Friedman and Johnson, 1988), and in rodents in 1996 (Brown-Borg et al, 1996). Whereas most genetic manipulations in rodents have been tested only once, with limited phenotypic assessment, the effects of DR have been tested in hundreds of labs, and its effects on nearly every age-related change have been documented (Baur, 2009; Masoro, 2005; Weindruch and Walford, 1988). The overwhelming conclusion is that DR affects something very fundamental to the aging process, as determined by its effects on disparate age-related diseases, as well as detailed analyses of mortality rates (Yen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, very little is known about the changes in physiology or intracellular signaling that accompany this effect. Interestingly, rapamycin was tested for effects on lifespan in part because it is proposed to mimic some of the signaling events triggered by caloric restriction (CR), which extends life in most species that have been tested ( Weindruch and Walford, 1988 ; Baur, 2009 ; Cox and Mattison, 2009 ). Two hallmarks of CR in rodents are improved insulin sensitivity ( McKee Alderman et al, 2010 ) and increased mitochondrial biogenesis ( Nisoli et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In essence, these preliminary studies suggested that DR could extend lifespan in rodents, and adumbrated more modern approaches. A wide variety of studies have shown this effect on lifespan, and also the beneficial effects of DR with regard to heart disease, cancer, neuroprotection and more (Baur, 2009;Masoro, 2005;Weindruch & Walford, 1988).…”
Section: Dr and Life Extension In Experimental Organismsmentioning
confidence: 98%